Growth Forms of Gardnerella spp. and Lactobacillus spp. on Vaginal Cells - Jung, Hyunsul; Ehlers, Marthie M.; Peters, Remco P. H.; Lombaard, Hennie; Redelinghuys, Mathys J.; Bezuidenhoudt, Johanna E.; Kock, Marleen M. (Frontiers in Cellular and Infection Microbiology, 2020)
Bacterial vaginosis (BV) is a common vaginal condition in women of reproductive age. During BV development, BV-associated bacteria may form a polymicrobial biofilm, which predispose women to recurrent BV. The aim of the study was to investigate the growth forms of Gardnerella spp. and Lactobacillus spp. and to determine the association between the bacterial growth forms and clinical characteristics [urinary tract infection (UTI) symptoms, human immunodeficiency virus (HIV) infection and abnormal vaginal discharge] in women attending a tertiary hospital in Pretoria, South Africa. A first-void urine specimen was collected from 196 women and BV was diagnosed using the Nugent scoring and the Ison-Hay criteria (vaginal smear microscopy). Fluorescence in situ hybridisation (FISH) was performed to classify the growth forms [“dispersed” or “biofilm”]. Bacterial cells were categorized as “dispersed” if cells were scattered separately and as “biofilm” if bacterial aggregates on the vaginal epithelial cells were observed. BV was detected in 52 women (52/196; 27%) and in these women, Gardnerella spp. were predominantly present in biofilms (46/52; 88% for Nugent scoring; and 45/50; 90% for Ison-Hay criteria), whereas Lactobacillus spp. were predominantly present in a dispersed form (38/52; 73% for Nugent scoring; and 37/50; 74% for Ison-Hay criteria). The odds of having BV increased when Gardnerella biofilms were present (p < 0.001), whereas the opposite was observed for Lactobacillus biofilms (p = 0.001). Neither Gardnerella spp. or Lactobacillus spp. (both dispersed or biofilms) had an association with the presence of UTI symptoms, HIV coinfection or abnormal vaginal discharge. In conclusion, this study demonstrated and confirmed that Gardnerella biofilms are associated with BV and that Lactobacillus spp. may form biofilms to protect against BV.